In the Flow of History and International Relations: A Theoretical Profile of Contemporary China - Orazio Maria Gnerre (Banber Arevelagitut'yan Instituti, 2025)
This paper intends to evaluate some elements that make up the worldview of contemporary China. To do this, these factors are dealt with (among others): the positioning that China assumes and wants to assume on the planet, and the ensemble of geopolitical theories that derive from it; and the conception of politics with respect to centralization / decentralization issues. In addition to this, the role of the economic (and geoeconomic) vision of contemporary China is also highlighted, in particular in relation to the thoughts of Xi Jinping expressed in 2017 at the Davos Forum. It becomes important to understand, in this sense, the idea of globalization and multipolarity that China extends, as a guiding principle, to its foreign policy. This is because this is based on cultural roots of distant ancestry. Through these interrelated interpretative levels, it is possible to understand the function that China plays within the contemporary world and its contribution of ideas and visions.